The rites of identity: the religious naturalism and cultural criticism of Kenneth Burke and Ralph Ellison - Eddy, Beth (Princeton University Press, 2003)
The Rites of Identity argues that Kenneth Burke was the most deciding influence on Ralph Ellison's writings, that Burke and Ellison are firmly situated within the American tradition of religious naturalism, and that this tradition--properly understood as religious--offers a highly useful means for considering contemporary identity and mitigating religious conflict. Beth Eddy adds Burke and Ellison to a tradition of religious naturalism that traces back to Ralph Waldo Emerson but received its most nuanced expression in the work of George Santayana. Through close readings of the essays and fictio